2013
DOI: 10.3324/haematol.2013.085506
|View full text |Cite
|
Sign up to set email alerts
|

Follicular lymphoma-like B cells of uncertain significance (in situ follicular lymphoma) may infrequently progress, but precedes follicular lymphoma, is associated with other overt lymphomas and mimics follicular lymphoma in flow cytometric studies

Abstract: ABSTRACTate lymphadenopathy, since the presence of a population of cells with an FL-like phenotype is often used to support the diagnosis of FL or one of the other GC-associated lymphoid neoplasms. Finally, because the proportion of overt FL preceded by FLBUS is not known, it remains to be established whether the situation is analogous to that of chronic lymphocytic leukemia where virtually all cases are preceded by monoclonal B-cell lymphocytosis.7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 39 publications
(53 reference statements)
1
42
0
2
Order By: Relevance
“…36 However, analogous to MGUS and MBL, retrospective review of "reactive" lymph nodes biopsied prior to a FL diagnosis has shown FLIS/FLBUS in a subset. 36,39 In approximately 15-20% of cases FLIS/FLBUS has been diagnosed in a lymph node involved by another B-cell lymphoma (Figure 1). 36,38,39 This finding might suggest that patients with FLIS/FLBUS are at increased risk, or it might be coincidental, due to the panel of immunostains routinely used to evaluate such biopsies.…”
Section: E Fmentioning
confidence: 99%
See 1 more Smart Citation
“…36 However, analogous to MGUS and MBL, retrospective review of "reactive" lymph nodes biopsied prior to a FL diagnosis has shown FLIS/FLBUS in a subset. 36,39 In approximately 15-20% of cases FLIS/FLBUS has been diagnosed in a lymph node involved by another B-cell lymphoma (Figure 1). 36,38,39 This finding might suggest that patients with FLIS/FLBUS are at increased risk, or it might be coincidental, due to the panel of immunostains routinely used to evaluate such biopsies.…”
Section: E Fmentioning
confidence: 99%
“…While one study found a correlation between the number of follicles involved by FLIS/FLBUS and the risk of subsequent lymphoma, 38 two other studies did not find the degree of involvement predictive of concurrent/subsequent lymphoma. 36,39 FLIS/FLBUS must be differentiated from partial involvement by low-grade follicular lymphoma (PFL), which usually shows partially effaced nodal architecture with enlarged, crowded follicles and attenuated mantle zones. …”
Section: Follicular Lymphoma In Situ/follicular Lymphoma-like Cells Omentioning
confidence: 99%
“…Furthermore, although very small B-cell clones carrying the t(14;18) translocation detectable by polymerase chain reaction (PCR) can frequently be found in the blood of healthy individuals 12 and follicular lymphoma in situ is a well recognized entity, 13 it is extremely rare for CD5 2ve clinical MBL to show the immunophenotypic or genetic features of a germinal-center-derived A.X., C.K., and A.G. contributed equally to this study.…”
Section: Introductionmentioning
confidence: 99%
“…Clonal relation of iFL and FL was suggested in one case and verified in another case by PCR amplification of the variable region of immunoglobulin heavy chain gene ( IgH ) and direct sequencing of its amplicons, respectively. Although a similar retrospective study has already been reported as a part of the large scale study by Pillai et al ,8 a clonal relation of iFL and FL has not been confirmed. Furthermore, we found that there appeared to be a reverse correlation between the rate of Bcl-2-positive follicles and time from surgery to diagnosis of FL.…”
Section: Introductionmentioning
confidence: 75%